Using Genomics to Shape the Definition of the Agglutinin-Like Sequence (ALS) Family in the Saccharomycetales - Oh, Soon-Hwan; Schliep, Klaus; Isenhower, Allyson; Rodriguez-Bobadilla, Rubi; Vuong, Vien M.; Fields, Christopher J.; Hernandez, Alvaro G.; Hoyer, Lois L. (Frontiers in Cellular and Infection Microbiology, 2021)
The Candida albicans agglutinin-like sequence (ALS) family is studied because of its contribution to cell adhesion, fungal colonization, and polymicrobial biofilm formation. The goal of this work was to derive an accurate census and sequence for ALS genes in pathogenic yeasts and other closely related species, while probing the boundaries of the ALS family within the Order Saccharomycetales. Bioinformatic methods were combined with laboratory experimentation to characterize 47 novel ALS loci from 8 fungal species. AlphaFold predictions suggested the presence of a conserved N-terminal adhesive domain (NT-Als) structure in all Als proteins reported to date, as well as in S. cerevisiae alpha-agglutinin (Sag1). Lodderomyces elongisporus, Meyerozyma guilliermondii, and Scheffersomyces stipitis were notable because each species had genes with C. albicans ALS features, as well as at least one that encoded a Sag1-like protein. Detection of recombination events between the ALS family and gene families encoding other cell-surface proteins such as Iff/Hyr and Flo suggest widespread domain swapping with the potential to create cell-surface diversity among yeast species. Results from the analysis also revealed subtelomeric ALS genes, ALS pseudogenes, and the potential for yeast species to secrete their own soluble adhesion inhibitors. Information presented here supports the inclusion of SAG1 in the ALS family and yields many experimental hypotheses to pursue to further reveal the nature of the ALS family.